2000
DOI: 10.1212/wnl.54.3.575
|View full text |Cite
|
Sign up to set email alerts
|

Fear recognition deficits after focal brain damage

Abstract: Fear recognition deficits in neurologic patients may be attributable to task difficulty factors rather than damage to putative neural systems dedicated to fear perception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
78
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(98 citation statements)
references
References 29 publications
16
78
1
1
Order By: Relevance
“…Emotions of disgust and anger were often confused with each other, as were the emotions of fear and surprise, and sad faces were often confused with neutral expressions. These patterns of errors were very similar to those reported in previous studies with normal adults (Anderson et al, 2000;Rapcsak et al, 2002). Surprise faces were mislabeled as fear but also as happy, revealing the ambiguous valence of this emotion.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Emotions of disgust and anger were often confused with each other, as were the emotions of fear and surprise, and sad faces were often confused with neutral expressions. These patterns of errors were very similar to those reported in previous studies with normal adults (Anderson et al, 2000;Rapcsak et al, 2002). Surprise faces were mislabeled as fear but also as happy, revealing the ambiguous valence of this emotion.…”
Section: Resultssupporting
confidence: 87%
“…The existence of specific anatomical substrates for individual emotions is a matter of debate (Calder et al, 2001;Rapcsak et al, 2002), and FTD is a progressive disease affecting mainly the frontal and anterior temporal regions (Bocti et al, 2004). FTD impairment in emotion recognition is likely to be caused by atrophy in orbitofrontal cortex, insula, and amygdala, and our study cannot address the unique contribution of these areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since it has been suggested that apparently selective impairments in recognition of specific emotions may be ascribed to different levels of task difficulty (Rapcsak et al, 2000), we aimed at verifying whether such a bias could account for LIS patients' impairment in recognizing negative emotions. To address this issue, we needed to refer to well established difficulty ratings for processing facial emotions.…”
Section: Task 1: Recognition Of Facial Expressionsmentioning
confidence: 99%